Investigating the Effect of Pressure on the Hugo Point on the Severity of a Headache after Head Injury - Mohammad Moradi; reza Zeighami; Hossein Tuzandeh jani; Mahmud Alipur (Journal of Research Development in Nursing and Midwifery, 2017)
Background: A headache is the most common post-traumatic complaint in patients. Nurses can help to relieve the pain and to improve the quality of the care through non-pharmacological methods. The aim of this study was to determine the effect of pressure on Hugo point on the severity of a headache after head injury. Methods: In this clinical trial, 60 patients were randomly divided into two intervention and control groups after accessible sampling. At first, the severity of a headache was measured by Visual Analogue Scale. In experimental group, the pressure was applied to Hugo point for 2 minutes followed by rest for 2 minutes; this procedure was repeated for 7 times. During this period, the control group received only routine care. The patients' pain scores were measured again after the intervention. Data analysis was performed using SPSS v.20 software. Results: There was a significant difference between the scores of pain in the experimental group before and after the intervention (P <0.05), however, this difference was not significant in the control group. Conclusion: Considering the ease of performing and the safety of this method, it is suggested to be used as an effective method to reduce the headache in patients.